시야결손 전 녹내장 환자의 광간섭단층촬영, 단파장시야측정, 주파수배가시야검사계 결과 - 권순일; Soon Il Kwon; 김윤정; Yun Jeong Kim; 정윤석; Yun Seok Chung (Daihan angwa haghoi jabji, 2007)
목적 : 시야결손 전 녹내장 환자를 대상으로 광간섭단층촬영(Optical Coherence Tomography; OCT)으로 측정한 유두주위 망막신경섬유층 두께를 알아보고, 단파장시야측정(Short Wavelength Automated Perimetry; SWAP), 주파수배가시야검사측정(Frequency Doubling Technology; FDT)을 실시하여 각각의 결과를 알아보고자 하였다. 대상과 방법 : 시신경유두사진에서 국소성 망막신경섬유층 결손을 보이나 표준자동시야검사에서 정상을 보이는 시야결손 전 녹내장 환자 36명 36안을 대상으로 전향적으로 OCT를 이용하여 유두주위 망막신경섬유층의 두께를 측정하고 이를 정상군 35명 35안과 비교하였다. 또한 SWAP, Matrix FDT 시야검사를 시행하여 각 검사간의 결과를 비교하였다. 결과 : 시야결손 전 녹내장 환자의 유두주위 망막신경섬유층 두께는 평균 93.40±11.16 um, 상측사분역 118.33±21.17 um, 하측사분역 108.72±16.76 um로 정상군에 비해 모두 통계적으로 유의한 감소를 보였고(P<0.05), Stratus OCT, SWAP, Matrix FDT 시야검사에서 각각 55.6%, 31.4%, 79.4%의 비정상 소견을 보였다. 결론 : 시야결손 전 녹내장 환자에서 OCT검사에서 유두주위 망막신경섬유층 두께의 감소를 보였고 Matrix FDT, OCT, SWAP순으로 민감도를 보였다. <한안지 48(7):935-941, 2007> Purpose: To evaluate the peripapillary retinal nerve fiber layer (RNFL) thickness with optical coherence tomography (OCT) in normal subjects and preperimetric glaucoma patients, as well as compare the results of OCT, short wavelength automated perimetry (SWAP), frequency doubling technology perimetry (FDT) in preperimetric glaucoma patients. Methods: Thirty-six eyes of 36 preperimetric glaucoma patients who have definitive localized RNFL defects in disc photograph and normal standard visual field, as well as 35 eyes of 35 normal subjects, were enrolled in this study. We compared the peripapillary RNFL thickness between the two groups using Stratus OCT. Stratus OCT, FDT, and SWAP results in preperimetric glaucoma group were also compared. Results: Compared with normal controls, peripapillary RNFL thickness, including the average, superior, and inferior quadrant, was significantly low (P<0.05) in the preperimetric glaucoma group, 93.40±11.16 um, 118.33±21.17 um, and 108.72±16.76 um respectively. In preperimetric glaucoma group, functional and structural abnormalities were found in 55.6% with Stratus OCT, 31.4% with SWAP, and 79.4% with Matrix FDT. Conclusions: Statistically significant reduction of RNFL thickness was revealed in the preperimetric glaucoma group, and Matrix FDT was the most sensitive test for detecting early glaucomatous change, followed by Stratus OCT, and SWAP. J Korean Ophthalmol Soc 48(7):935-941, 2007